Performance Research and Application Status of Fish-Bellied Prestressed Steel Support Structure System - Zhao, Zichen; Wu, Liwei (International Journal of Mechanical and Electrical Engineering, 2025)
With the advancement of urbanization, in the field of modern construction engineering, especially in the deep foundation pit support system, the requirements for deformation control of foundation pit are constantly improving, and the focus of foundation pit support is also more biased towards stiffness control under the condition of engineering safety. Compared with the traditional concrete support, the fish-bellied prestressed steel support system is composed of fish-bellied prestressed steel support, corner brace, brace, triangular connecting member and vertical column. As a kind of assembled large stiffness internal support system, it has obvious advantages in safety, excavation space, convenient disassembly and assembly, construction period, economy and green environmental protection, and is widely used. In order to understand the research progress of existing scholars on fish-bellied prestressed steel support, this paper first summarizes the research and application status of common assembled horizontal support and assembled vertical support structure, and summarizes the shortcomings of current research. Through in-depth research on existing literature, patents, specifications and standards, the research status of fish-bellied prestressed steel support is emphatically analyzed. The basic principle, force transmission system and application status of fish-bellied prestressed steel support system are introduced. So as to reveal the variation law of support structure stress and foundation pit displacement. Summarize the shortcomings of the system research, and give targeted suggestions and future research directions